Student’s Coaching During the Covid-19 Pandemic in the SMAN 1 Rupat: National Science Competition in 2021 - Surya Aymanda Nababan; Pulung Sumantri; Yushar Tanjung; Anju Nofarof Hasudungan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to describe the results of observations regarding the implementation of club management at SMAN 1 Rupat KSN in 2021 during the Covid-19 pandemic. KSN is an abbreviation of the National Science Competition which is carried out by the National Achievement Center of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. The selection mechanism for the implementation of KSN is carried out starting at the school, district/city, provincial, national, and international levels. In the achievement of KSN, schools located in the capital city of Riau province, Pekanbaru, and with good facilities, and inputs dominate. SMAN 1 Rupat is located on Rupat Island, precisely in Batu Panjang Village, Rupat District, Bengkalis Regency, Riau Province. This island is included in the 3T category area (Lagged, Foremost, and Outermost) which is directly opposite the Malaysian state and is a challenge in itself in the achievement of KSN. The research used is descriptive qualitative research. Data was collected by interview, literature study, document analysis and observation. The results of the study indicate that the management of the principal and students is the main key to achieving the best results in the midst of limited school facilities and infrastructure and Rupat as a 3T area.